Meninas, jovens e velhas : personagens tecidas na narrativa de Helena Parente Cunha - Lima, Lílian Almeida de Oliveira (2014)
The thesis Girls, young and old: characters woven into the narrative of Helena Parente Cunha is based on studies about the relationship between literature, women and gender relations. We examine the female characters present in the fictional work of Brazilian writer Helena Parente Cunha, comprising of the following titles: Os provisórios (1980), Mulher no espelho (1983), Cem mentiras de verdade (1985), As doze cores do vermelho (1989), A casa e as casas (1996), Vento, ventania, vendaval (1998), Claras manhãs de Barra Clara (2002), Falas e falares (2011). To describe these female characters and their behavioral patterns under the influence of gender formats and the structures of male domination, we dialogue with theoreticians from different areas, such as Teresa de Lauretis and her concept of the "technology of gender"; Elaine Showalter and her "cultural model of female writing", which reveals a double-bladed discourse, of the dominant and of the silenced voices. We also refer to Pierre Bourdieu s ideas and other theoretical discussions about male domination. For our analysis, the characters are grouped into age groups ranging from childhood through their youth to maturity, reaching old age, owing to the fact that gender frameworks are disseminated from an early age and reverberate throughout a lifetime. For each age group, we present a chapter investigating the structures of domination and symbolic violence that girls and young, mature and old women are submitted to, revealing not only the double discourse mentioned above, but also the consent of the women to the dominant power